Mother–infant attachment, musical idol worship, and the origins of human behaviour. (December 2018) - Parncutt, Richard
Actors, sportspeople, and politicians may be idolised for their appearance, personality, skills, or ideals. The idolisation of musicians additionally involves transcendental musical emotions. Fans devote extraordinary amounts of time, energy and money to following, empathising with, identifying with and imitating their idols. During great performances, fans experience altered states of consciousness. Existing evolutionary approaches can explain social dominance hierarchies but not specific fan behaviours. Another approach involves the mother schema : the perceptions, cognitions, and emotions that the late foetus and early infant (3rd and 4th trimesters) associate with the mother and her changing behaviours and physical/emotional states. The mother schema was an evolutionary response to the fragility (altriciality) of human infants, born earlier due to a larger brain and upright gait. Active reciprocal interactions between infants and carers (e.g. motherese) involve both the carer's infant schema and the infant's mother schema. In later life, the typical emotions of the mother schema are evoked by stimulus patterns reminiscent of the mother as perceived by the infant. In ritual situations, where the focus is on shared subjectivity, similar patterns and emotions are created. Evolutionary by-products of the mother schema include musical behaviours, religious behaviours and musical idol worship. The theory can explain why musical idols are perceived as all-loving, all-knowing and/or all-powerful, and is consistent with psychosocial functions of music and religion such as social cohesion and identity, collective motivation, empathy and mood regulation, catharsis and coping, distraction and entertainment, conflict resolution, and skill transfer.